Evaluasi Praktik Green Supply Chain Management Pada PT Semen Padang dengan Pendekatan TRIZ-DEMATEL - Yelita Anggiane Iskandar; Resha Khairunnisa (Fakultas Teknik Universitas Persada Indonesia YAI, 2026)
PT Semen Padang, as a company in the cement industry, has implemented Green SupplyChain Management (GSCM); however, its implementation still faces various operationalchallenges. This study aims to identify contradictions in the implementation of GSCM andto determine priority improvement strategies that can be applied effectively. The methodsused in this study are a combination of Theory of Inventive Problem Solving (TRIZ) andDecision-Making Trial and Evaluation Laboratory (DEMATEL). The identification ofcontradictions was carried out through internal questionnaires using the TRIZ approachand resulted in nine contradictions across the aspects of green purchasing, greenmanufacturing, and green distribution. Based on these contradictions, inventive solutionswere formulated and further analyzed using DEMATEL to map cause-effect relationshipsand determine strategic priorities. The results indicate that strategy (A2) in the greenpurchasing aspect and strategy (G4) in the green manufacturing aspect are the main causefactors with the strongest influence, with ?? − ?? values of 1.166 and 1.489, respectively.These priority strategies are expected to enhance the effectiveness of GSCMimplementation at PT Semen Padang in a sustainable manner